“Dinámica de poblaciones de insectos plagas y benéficos en el cultivo de la tara (caesalpinia spinosa) bajo un sistema de riego por goteo con aguas residuales en el distrito de lurín-Lima” - Bocanegra Calampa, Jorge Isaacs (2012)
This research was conducted in the district Lurin (Lima) during the months of September 2011 to February 2012, had as main objective to determine the population dynamics of insects present in "tara". The methodology used was for weekly assessments of insect pests and beneficia! to determine their taxonomic position, which was supported by SENASA Lima. The conditions of the experimental plot was sandy soil through drip irrigation with wastewater from the oxidation pond in the district of Lurin, as interday, no insecticides were applied. The plantation Tara was an age of 2 years and the distribution of the plots were randomly selected from 5 plots with 9 floors each, which were evaluated as a whole. The results obtained during the experiment focused on two parameters, presence of pests and their fluctuation and the presence of beneficia! insects. We found the following pests: Melipotis famelica Guenee, 1821 (Lepidoptera: Ophiderinae) known as high-sheet Eurisacca melanocampta Meyrick (S I O) called stem borer; Empoasca kraemeri (Hemiptera: Cicadellidae) known as a sharpshooter; Macrosiphon sp and Aphis craccivora (Hemiptera: Aphididae) known as afidos, whiteflies sort of unidentified generic level, belonging to the arder Hemiptera and family Aleyrodidae, and beneficia! insects as follows: Eriopis connexa (Germar, 1824), Cicloneda sanguine (Linnaeus, 1743 ), Hippodamia convergens Guérin Menésville 1842, Harmonia axridis (Pallas, 1772) ( Coleoptera: Coccinellidae ), Podisus nigrispinus Dallas, 1851 (Hemiptera: Pentatomidae ), Chrysoperla asoralis (Banks, 1915), Chrysoperla externa (Hageh, 1861) (Neuroptera : Chrysopidae). Of insects identified, notably emphasizes the presence of the family Cicadellidae arder Hemiptera with Empoasca kraemeri species having a substantial population growth and coincident with increasing temperatura, which is observad during December 2011 and February 2012 months. Keywords Tara, Caesalpinea, insect pests, predators, insect orders, familias, taxonomic classification